Slavery and frontier Mississippi, 1720-1835 - Libby, David J., 1969- (University Press of Mississippi, 2004)
American history -- African American studies -- & In the popular imagination the picture of slavery, frozen in time, is one of huge cotton plantations and opulent mansions. However, in over a hundred years of history detailed in this book, the hard reality of slavery in Mississippi's antebellum world is strikingly different from the one of popular myth. It shows that Mississippi's past was never frozen, but always fluid. It shows too that slavery took a number of shapes before its form in the late antebellum mold became crystalized for popular culture. The colonial French introduced African sla.